Effects of simple knee sleeves on pain and knee adduction moment in early unilateral knee osteoarthritis - Mohd Sharif, Nahdatul Aishah; Usman, Juliana; Wan Safwani, Wan Kamarul Zaman; Goh, Siew Li; Abdul Karim, Samihah; Mohamed, Nur Anisah; Khan, Soobia Saad; Khan, Saad Jawaid (SAGE Publications, 2019)
Knee sleeves are often prescribed to alleviate pain in people with early knee osteoarthritis. However, the biomechanics underlying their pain-relieving effect are still not well understood. This pre–post study aims at evaluating and comparing the effects of two different types of knee sleeves on knee adduction moment. Patients with clinically diagnosed knee osteoarthritis were recruited from the University of Malaya Medical Centre and were randomly assigned to two test groups using (1) a simple knee sleeve and (2) a simple sleeve with patella cutout. Knee adduction moment was collected using the Vicon motion capture system with two Kistler force plates. Pain, stiffness and physical functions were recorded using the Western Ontario and McMaster Universities Osteoarthritis Index. All measurements were taken before, immediately after and at the completion of 6 weeks of application (primary time point). In total, 17 participants with early unilateral knee osteoarthritis (47.7 (9.7) years) completed the study. Overall results show significant reduction in pain, early stance and late stance knee adduction moment and increased walking speed after 6 weeks of both knee sleeves application. This study results suggest that knee sleeves can reduce knee adduction moments in early unilateral knee osteoarthritis by 14.0% and 12.1% using the simple sleeve and the sleeve with patella cutout, respectively, and can potentially delay disease progression. In addition, knee sleeve with patella cutout does not provide additional benefits when compared to the simple knee sleeve. © IMechE 2019.